Faktor yang Berhubungan dengan Tingkat Pengetahuan Orang Tua Tentang Pendidikan Seks Secara Dini pada Anak Sekolah Dasar (SD) - Maryuni Maryuni; Legina Anggraeni (Alma Ata University Press, 2016)
Indonesian Child Protection Commission states that at least 45 children who are victims of sexual violence every month. Early sex education for children is essential to prevent sexual violence but many parents have opinion that sex education for children are taboo. This study aims to determine what factors are associated with the level of knowledge of parents against early sex education for children. This research was conducted in Primary School Kartika VIII-5, South Jakarta 2014. This research is descriptive analytic with cross sectional approach. The population in this study are parents of students in grade 1 in Primary School Kartika VIII-5 South Jakarta. Samples were selected by total sampling method resulting on 60 respondents. Collecting data using questionnaires. Data analysis techniques using chie square. Results showed that there were a significant relationship between education, social and cultural values, and exposure information with knowledge about sex education at an early stage, while the work are not related. In conclusions, this study factors was correlated with parents knowledge about early sex education for children in Primary School Kartika VIII-5 were education, social and cultural values, and exposure information. Expected for parents to improved information about early sex education for children, so parents have good knowledge abou t sex education.